2021
DOI: 10.24246/j.js.2021.v11.i1.p37-46
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Pemahaman Kognitif Dan Kesulitan Belajar Matematika Konsep “Logika” Dengan Model Pembelajaran Daring

Abstract: This study aims to describe the results of the analysis of cognitive comprehension abilities and learning difficulties in mathematics logic subject using the online learning model for PGSD students at Sanata Dharma University. The research method used is descriptive research method. The research involved PGSD students of Sanata Dharma University in 2020/2021 with data collection techniques and information through a student response questionnaire instrument and cognitive ability test questions using Google form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 6 publications
(7 reference statements)
0
8
0
8
Order By: Relevance
“…Different aspects of the students' perspective were covered. In terms of the cognitive aspect, several studies focused on viewing students' mathematics competencies, namely problem-solving (Kusmaharti & Yustitia, 2020), mathematical communication (Sari et al, 2020), conceptual understanding (Anugrahana, 2021), and mathematical reasoning (Sugandi & Bernard, 2020). Other studies revealed common purposes related to mathematics learning outcomes (Sari et al, 2020) and learning di culties (Anugrahana, 2021) during the pandemic.…”
Section: Indonesian Issues Of Online Mathematics Learning During the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Different aspects of the students' perspective were covered. In terms of the cognitive aspect, several studies focused on viewing students' mathematics competencies, namely problem-solving (Kusmaharti & Yustitia, 2020), mathematical communication (Sari et al, 2020), conceptual understanding (Anugrahana, 2021), and mathematical reasoning (Sugandi & Bernard, 2020). Other studies revealed common purposes related to mathematics learning outcomes (Sari et al, 2020) and learning di culties (Anugrahana, 2021) during the pandemic.…”
Section: Indonesian Issues Of Online Mathematics Learning During the Pandemicmentioning
confidence: 99%
“…Educators should prepare online learning tools well to maximize the capacity of learners in solving problems. (Anugrahana, 2021) According to Bloom's Taxonomy, the analysis of students' cognitive abilities was measured by tests that met the standard of cognitive dimensions, but student completion results were still below 50%.…”
Section: Not Applicablementioning
confidence: 99%
“…Keberhasilan tersebut dapat pula dicapai dengan aspek kognitif yang mana dibutuhkan dalam kemampuan pemecahan masalah. Aspek kognitif mencakup hubungan siswa dalam memahami masalah secara bertahap (Anugrahana, 2021). Ketika pembelajaran daring, seringkali siswa mendapat banyak kendala baik jaringan internet maupun pemahaman materi.…”
Section: Generalityunclassified
“…Secara garis besar ada dua jenis kesulitan dalam pembelajaran online, yakni kesulitan pemahaman konsep terkait materi matematika dan kesulitan kendala teknis, hal ini sejalan dengan penelitian yang dilakukan (Anugrahana, 2021). Dalam penelitian (Simanjuntak & Harahap, 2020;Turmuzi et al, 2021; Utami, Y. P., & Cahyono, 2020) mengungkap bahwa kendala terbesar dalam pembelajaran online adalah teknis signal dan ketidakmampuan dalam belajar online.…”
Section: Stakeholder Yang Membantu Pemerintah Sekolah Dan Wali Murid Dalam Pembelajaran Onlineunclassified